2001
DOI: 10.1890/0012-9658(2001)082[2101:dadots]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and Distribution of Tree Species in Upper Amazonian Terra Firme Forests

Abstract: Amazonian forests are the largest and most diverse in the tropics, and much of the mystery surrounding their ecology can be traced to attempts to understand them through tiny local inventories. In this paper we bring together a large number of such inventories scattered across immense areas of western Amazonia in order to address simple questions about the distribution and abundance of tropical tree species in lowland terra firme forests there. The goal is to describe patterns of commonness and rarity at local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
500
10
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 498 publications
(566 citation statements)
references
References 47 publications
30
500
10
26
Order By: Relevance
“…Previously, when forest ecologists looked at the Amazon Basin they saw complexity, not pattern. After examining tree-distribution data more closely, however, Pitman et al (2001) found that the common trees formed predictable oligarchic hierarchies that were present across the complex landscape. In both their Ecuador and Perú plots, they found dozens of common species and hundreds of rare species.…”
Section: Characterization Of Typical Lowland Rainforest Composition Imentioning
confidence: 99%
“…Previously, when forest ecologists looked at the Amazon Basin they saw complexity, not pattern. After examining tree-distribution data more closely, however, Pitman et al (2001) found that the common trees formed predictable oligarchic hierarchies that were present across the complex landscape. In both their Ecuador and Perú plots, they found dozens of common species and hundreds of rare species.…”
Section: Characterization Of Typical Lowland Rainforest Composition Imentioning
confidence: 99%
“…Luego de calcular la biomasa aérea de cada árbol, se transformaron los resultados a toneladas por hectárea. Finalmente, se compararon gráficamente los datos con los de los bosques amazónicos maduros de tierra firme reportados por Pitman et al (2001), Baker et al (2004), Pallqui et al (2014) para ilustrar cambios en la sucesión secundaria asociados a la historia de uso del suelo.…”
Section: Emplazamiento De Las Parcelas Mediciones De Los áRboles Y Punclassified
“…P(mad) = datos de Tambopata-Madre de Dios, Perú (Pallqui et al 2014; n = 9 parcelas). E,P(mad) = datos de Yasuní y Manu (Ecuador y Perú respectivamente) (Pitman et al 2001; n = 26 parcelas). Bo, Br, E, P(mad) = datos de Bolivia, Brasil, Ecuador y Perú (Baker et al 2004; n = 44 parcelas).…”
Section: Parcelaunclassified
See 2 more Smart Citations